2021
DOI: 10.1039/d1tb00454a
|View full text |Cite
|
Sign up to set email alerts
|

A double-layer dura mater based on poly(caprolactone-co-lactide) film and polyurethane sponge: preparation, characterization, and biodegradation study

Abstract: Synthetic, biodegradable polymer holds a great potential in dura mater substitution. In this study, a dura mater-mimetic double-layer film@sponge composite was developed. The composite contains a poly(caprolactone-co-lactide) (PCLA) film and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The T g of PLLA, PCL and PVP were measured as 54.3 °C, −61.9 °C and over 120 °C in previous studies, respectively. 23–25 As shown in Table 1, each sample was only detected a single glass transition, which was belonged to random copolymers of network. These results indicated that components were homogeneously incorporated into the network structure.…”
Section: Resultsmentioning
confidence: 99%
“…The T g of PLLA, PCL and PVP were measured as 54.3 °C, −61.9 °C and over 120 °C in previous studies, respectively. 23–25 As shown in Table 1, each sample was only detected a single glass transition, which was belonged to random copolymers of network. These results indicated that components were homogeneously incorporated into the network structure.…”
Section: Resultsmentioning
confidence: 99%
“…The composite nanofibers from natural and synthetic polymers have shown desired structures and material properties for biomedical applications, including dural repair. Natural materials provide favorable biological properties, whereas synthetic materials provide mechanical strength [ 111 , 112 ]. In addition, the fabrication of a multilayered structure could mimic the microarchitecture and multiple functions of native dura mater.…”
Section: Biomedical Applications Of Electrospun Nanofibersmentioning
confidence: 99%
“…Hemstapat et al 76 in vitro ORC knitted fabric/PCL knitted fabric composites tensile properties and stitch tear strength of the composites are closer to those of human cadaveric dura mater than dense-type and porous-type dural substitutes. Meanwhile, the water-tightness performance of composites was inferior to that of cadaveric dura mater but better than that of commercial dural substitutes Chuan et al 64 in vitro stereocomplex poly(lactic acid) nanofibers the ultimate tensile strength and the elongation break of the nanofiber membranes were close to those of human dura matter, and the nanofiber membranes showed neuron compatibility on marrow stem cells without toxic effects Li et al 77 in vitro and rabbit model acellular swim bladder (ASB) ASBs avoided the leak of CSF with neither hemolysis, brain adhesion, severe inflammation, nor fibrosis, allowed cells to attach and migrate on its surface or interior, and gradually reestablished tissue structure and function Xu et al 78 in vitro and rabbit model vancomycin-loaded bacterial cellulose sustained release of vancomycin bacterial cellulose can improve the central system infection after implantation effectively and repairs dural defect in rabbit Pogorielov et al 41 in vitro and rabbit model chitin−chitosan graft chitin−chitosan graft is more effective to close the dura mater defect compared to fascia lata, has an antibacterial effect, and can support cell viability to prevent adhesion scar formation and ensure tightness of the subdural space Jin et al 79 in vitro and rat model poly(caprolactone-colactide) (PCLA) film and polyurethane (PU) sponge composite integrated the mechanical properties of the films and the water absorption of the sponge, and the biocompatibility and biodegradability of the PCLA and PU composites were verified by in vitro degradation and cytotoxicity study and the in vivo implantation in rats Natural materials such as collagen membranes do not produce severe chronic inflammatory reactions, but the degradation rate is uncontrollable so new meninges are often unformed after the material has degraded. Meanwhile, the material is brittle and easily broken or tears during suturing causing CSF leakage.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…graft chitin−chitosan graft is more effective to close the dura mater defect compared to fascia lata, has an antibacterial effect, and can support cell viability to prevent adhesion scar formation and ensure tightness of the subdural space Jin et al79 in vitro and rat model poly(caprolactone-colactide) (PCLA) film and polyurethane (PU) sponge composite integrated the mechanical properties of the films and the water absorption of the sponge, and the biocompatibility and biodegradability of the PCLA and PU composites were verified by in vitro degradation and cytotoxicity study and the in vivo implantation in rats h i b i t e d .…”
mentioning
confidence: 99%